Multiple air pollutant exposure is associated with higher risk of all-cause mortality in dialysis patients: a French registry-based nationwide study - Hamroun, Aghiles; Génin, Michaël; Glowacki, François; Sautenet, Bénédicte; Leffondré, Karen; De Courrèges, Antoine; Dauchet, Luc; Gauthier, Victoria; Bayer, Florian; Lassalle, Mathilde; Couchoud, Cécile; Amouyel, Philippe; et al. (Frontiers in Public Health, 2024)
Little is known about the effect of combined exposure to different air pollutants on mortality in dialysis patients. This study aims to investigate the association of multiple exposure to air pollutants with all-cause and cause-specific death in dialysis patients. Material and methods. This registry-based nationwide cohort study included 90,373 adult kidney failure patients initiating maintenance dialysis between 2012 and 2020 identified from the French REIN registry. Estimated mean annual municipality-levels of PM2.5, PM10 and NO2 between 2009 and 2020 were combined in different composite air pollution scores to estimate each participant's exposure at the residential place one to three years before dialysis initiation. Adjusted cause-specific Cox proportional hazard models were used to estimate hazard ratios per interquartile range (IQR) greater air pollution score. Effect measure modification was assessed for age, sex, dialysis modality, and baseline comorbidities.Results. Higher levels of the main air pollution score were associated with a greater rate of allcause deaths (HR, 1.082 [95% CI, 1.057-1.104] per IQR increase), regardless of the exposure lag. This association was also confirmed in cause-specific analyses, most markedly for infectious mortality (HR, 1.686 [95% CI, 1.470-1.933]). Sensitivity analyses with alternative composite air pollution scores showed consistent findings. Subgroup analyses revealed a significantly stronger association among women and less comorbid patients. Discussion. Long-term multiple air pollutant exposure is associated with all-cause and causespecific mortality among patients receiving maintenance dialysis, suggesting that air pollution may be a significant contributor in the increasing trend of CKD-attributable mortality worldwide.